2004
DOI: 10.5194/angeo-22-4291-2004
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmasphere Boundary Layer

Abstract: Abstract.As an inner magnetospheric phenomenon the plasmapause region is of interest for a number of reasons, one being the occurrence there of geophysically important interactions between the plasmas of the hot plasma sheet and of the cool plasmasphere. There is a need for a conceptual framework within which to examine and discuss these interactions and their consequences, and we therefore suggest that the plasmapause region be called the Plasmasphere Boundary Layer, or PBL. Such a term has been slow to emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
117
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(117 citation statements)
references
References 82 publications
0
117
0
Order By: Relevance
“…Density irregularities exist inside the plasmasphere measured by Cluster (Darrouzet et al, 2004). The small-scale density structures inside PBL (plasmasphere boundary layer) are one of the research topics discussed by Carpenter and Lemaire (2004). Goldstein et al (2004) reported density fluctuations detected by LANL (Los Alamos National Laboratory) geosynchronous satellites.…”
Section: Introductionmentioning
confidence: 99%
“…Density irregularities exist inside the plasmasphere measured by Cluster (Darrouzet et al, 2004). The small-scale density structures inside PBL (plasmasphere boundary layer) are one of the research topics discussed by Carpenter and Lemaire (2004). Goldstein et al (2004) reported density fluctuations detected by LANL (Los Alamos National Laboratory) geosynchronous satellites.…”
Section: Introductionmentioning
confidence: 99%
“…The outer boundary of the plasmasphere, called the plasmapause, represents the cutoff in the plasma density, the location of which depends on the level of the geomagnetic disturbances. In the equatorial plane the plasmapause is typically found near 5-7 R E (e.g., Chappell et al, 1970a;Carpenter and Lemaire, 2004;Pedatella and Larson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1.1.3. Asymmetric Whistler Observation Across Plasmasphere Boundary Layer Both ground-based [Carpenter et al, 1968;Carpenter and Ć ulić, 1988] and space-based [Platino et al, 2005, and references therein] observations of lightning-generated, ducted whistlers have clearly demonstrated an asymmetry in the observations across the plasmasphere boundary layer [Carpenter and Lemaire, 2004]. While observation of whistlers inside of the plasmasphere is a common occurrence, the same does not hold true beyond the plasmapause boundary layer.…”
Section: Source Regionmentioning
confidence: 91%
“…The outer boundary of the plasmasphere, often referred to as the plasmapause [e.g., Lemaire and Gringauz, 1988] or the plasmaspheric boundary layer [Carpenter and Lemaire, 2004], is typically characterized by an abrupt 1 to 2 orders of magnitude decrease in plasma density as a function of geocentric distance. The exception to this typical picture of the plasmapause occurs during extended periods of geomagnetic quiescence.…”
Section: The Plasmaspherementioning
confidence: 99%